High return to play rate following treatment of multiple-ligament knee injuries in 136 elite athletes - Borque, K. A.; Jones, M.; Balendra, G.; Willinger, L.; Pinheiro, V. H.; Singh Anand, B.; Williams, A. (Knee surgery, Sports Traumatology. Arthroscopy, 2022)
Purpose: The purpose of the study is to assess return to play rate and timing of elite athletes treated for multi-ligament knee injuries with modern surgical techniques. Methods: A retrospective review was performed of all professional or national/international level athletes treated for a multi-ligament knee injury by the senior author in the period from February 2001 to October 2019, with a minimum of 2-year follow-up. The study cohort consisted of 136 elite athletes who underwent surgery of two or more knee ligaments. Outcomes measures were return to play (RTP), defined as return to elite level sport, return to play time, and further surgical procedures. Results: One hundred and twenty (88.2%) athletes returned to elite level sport at an average of 12.8 months from operation. In unicruciate injuries, ACL and PCL-based injuries had similar return to play rates (89.1% vs. 87.5% respectfully, n.s.) although mean RTP time was longer in those with PCL-based injuries (15.2 vs. 11.9 months, p < 0.01). Bicruciate injuries had longer RTP times compared to unicruciate injuries (mean RTP 16.0vs. 12.4 months, p < 0.05) but were able to return at a similar rate (83.3% vs. 88.9%, n.s.). Medial and lateral sided injuries had similar RTP rates (89.3% vs. 87.9%, n.s.) though lateral sided injuries took longer before returning to play (13.4 vs. 11.6 months, p < 0.05). Further surgery was required in 54 (39.9%) patients including 25 (18.4%) manipulations under anaesthesia. Four (2.9%) of the athletes underwent revision ligament surgery. Conclusion: Modern surgical techniques used in the treatment of multi-ligament knee injuries can lead to high return to play rates in elite athletes.